Pharmacotoxicology of Non-fentanyl Derived New Synthetic Opioids - Solimini, Renata; Pichini, Simona; Pacifici, Roberta; Busardò, Francesco P.; Giorgetti, Raffaele (Frontiers in Pharmacology, 2018)
A class of opioid agonists not structurally related to fentanyl, derived from research publications of pharmaceutical companies or patents within the US and abroad are contributing to the current opioid epidemic. Novel synthetic opioids (NSOs) created to circumvent drug control laws such as U-47700, U-49900, AH-7921 or MT-45 have no recognized therapeutic use, are clandestinely manufactured and sold on conventional or dark web. We herein provide a review of the pharmacological properties available on most of these substances trying to provide a better knowledge on these compounds, particularly with respect to toxicity and dangerous adverse effects in users. Indeed, these NSOs share not only a great potency of action and receptor affinity with respect to natural or synthetic opiates (e.g. morphine, heroin, methadone) but also a non-negligible toxicity leading to intoxications and fatalities, posing a serious harm to public health and society.